Memórias da escola Nossa Senhora de Lourdes, RS: narrativas da experiência educativa em uma instituição confessional católica (1960-1970) - Velasquez, Cinára Dalla Costa (2016)
The purpose of this Thesis was to show a study about the educational history in Rio Grande do Sul, specifically, within the catholic confessional education and the students educational formation, in a boarding school, which was organized by the Imaculado Coração de Maria Sisters from 1892 to 1980. It were problematized the subject s memories that lived the formation as boarders, in a catholic religion private school, in a community from Vale Vêneto in a Rio Grande do Sul central region. People that lived the specifically educational experience, they were students from a catholic confessional school with mixed boarding school. Such specificity stands up because the mixed boarding is characterized by a diferential trace, in the interior of Rio Grande do Sul s state, it wasn t offered this kind of boarding school. From the analyses of different storage media, written, visuals and orals, about the history of the school, evidences indicated that school consolidation, since the decade of 1954, when it started to offer junior high school, transforming itself in a first catholic religious high school with a mixed boarding, in the interior of Rio Grande do Sul. By following this reasoning and from this intersection of different memorialistic documents analyzed, as draft, chronic books, school and students pictures and the oral narratives done by a methodological approach by the oral history, it allowed to notice that it became a remarkable school because it had being a confessional and offering a mixed school that accepted both genders as students. A scholar institution that received its students in an internal condition with a different profile, because they were from different places in the state, which turn it an Educated Education space with strong cultural hybrid, and also, understood as a total institution by closing trace representation that it established the student and contributor s narratives, internal in the period from 1960 to 1970, markedly the isolation and family separation emerge with acute critical woven for them. It interested me to understand how the ex-students narrative memories were built/ the recompose the educational experience in a college / Catholic boarding school and gives way to such training , either in your personal or professional experiences ?The student s memory building, from the representations produced in the interviews showed that the educational experience educated and the formation that they received were produced when they were boarders shows narrative thread of thanks as discipline, although recognized as being extremely rigid, brought them lessons for their personal and professional lives, the values embodied in their lives, such as limits, the organization, are heavily credited to this rigorous disciplinary training; paradoxically bring the critical tone about the closure, especially on the isolation and longing for the family, this seems to be the sad mark of your images-memories woven light of that past. The research allowed pointing out that the memory is woven through the evocation of an experience in a group in an institution and bears the marks of the team, so the memory of the College boarding Sisters - well expressed by them- brought the marks. A memory community, graduates who lived in the school admitted on condition; memories profiled in a strong narrative thread that says the feeling of belonging to the school and the recognition and gratitude to training, but the longing and isolation, brought, also, the critical tone.